Globalisation of production and markets - Peter Nunnenkamp; Erich Gundlach; Jamuna Prasad Agarwal (Mohr; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1994)
Since the 1980s, competitive pressure has increased in the world economy. In addition to traditional trade flows, the globalisation of production and markets has greatly enhanced the complexity of the international division of labour. Declining transaction and information costs have stimulated the fragmentation of production processes on a worldwide scale and the relocation of noncompetitive industries. As a result, in both industrialised and developing countries, newly emerging competitors have increasingly challenged established suppliers. The aim of this study is threefold. First, the authors portray the trend towards globalisation and assess by which means enterprises have gone global. Second, they discuss the adjustment needs of traditional producers by evaluating the consequences of globalisation on trade, production, employment and wages. Third, they analyse whether the economic policy reactions to globalisation in industrialised countries are adequate to deal efficiently with competitive challenges. It turns out that the scope of national policies has been significantly reduced by globalised production and markets, while corporate strategies have increasingly been less constrained. Consequently, major policy revisions are indispensable. Most importantly, governments in industrialised countries should focus their attention on human capital formation, rather than on defensive trade policies, whose effectiveness has been seriously eroded. This study is part of a research project on "The Social Market Economy: Challenges and Conceptual Response".
Keywords: 330; Internationale Arbeitsteilung; Direktinvestition; Internationale Unternehmenskooperation; Industriegüteraußenhandel; Internationaler Wettbewerb; Welt; EU-Staaten; USA; Japan